The Effect of Guided Inquiry Laboratory Activity with Video Embedded on Students’ Understanding and Motivation in Learning Light and Optics - Tina Afriani; Rika Rafikah Agustin; Eliyawati Eliyawati (Universitas Pendidikan Indonesia, 2019)
This research aims to investigate the effect of guided inquiry laboratory activity with video embedded on students’ understanding and students’ motivation in learning lights and optics topic. The method used in this research was pre-experiment. The sampling technique used in this research was convenience sampling, and the samples were taken from grade 8 in one of junior high school in Bandung. The sample was 20 students. The class implemented guided inquiry laboratory activity with video embedded in learning light and optics. The students’ understanding was measured using test given at pretest and post-test while students’ motivation was calculated using software ministeps (RASCH Model). The t-test paired sample also was performed on the average level of 95% to identify the significant difference of students’ understanding before and after the implementation of guided inquiry laboratory activity with video embedded. The results of this research show that the use of guided inquiry laboratory with video integrated gives an improvement of students understanding. Even though the value of n-gain is 0,264 (categorized as low level), the statistical test shows that there is a significant difference between students understanding before and after the implementation of guided inquiry laboratory activity with video embedded. There are 15 students from 20 students who are motivated in learning light and optics by using guided inquiry laboratory activity with video embedded. Students are motivated by the implementation of guided inquiry laboratory activity with video embedded.